Pengaruh store atmosphere terhadap keputusan pembelian konsumen di Coffee Shop Lucky Coffee Kota Jambi - Krisito, Renol Elmi; Yacob, Syahmardi; Yuniarti, Yenny (Jurnal Dinamika Manajemen, 2020)
This study aimed to determine the effect of store atmosphere dimensions on purchasing decisions at Lucky Coffee Jambi City coffee shop. The number of samples taken was 100 respondents using nonprobability sampling techniques and quantitative methods. Data collection was carried out by distributing questionnaires. Based on the study results, it is suggested that Lucky Coffee keep the outside variable (X1) and purchase points (X4) to increase consumer purchasing decisions on Lucky Coffee. Data were analyzed with multiple linear regression analysis using statistical software SPSS 21. The results showed that the coefficient of determination showed an R square of 0.752, which means that the store atmosphere affects purchasing decisions by 75.2%. The remaining24.8% is influenced by other factors not examined in this research. The F Store Atmosphere test involves purchasing decisions, evidenced by the F value of 71.834. In the T-test, it is known that the exterior (X1) has an effect of 5.346, the general interior (X2) is 1.315, the store layout (X3) is 0.423, and the point of purchase (X4) is 2.079. From the results of this study, it can be concluded that the Store Atmosphere on individual purchasing decisions affects the outer dimensions of the store and the purchase points. In contrast, the general interior dimensions and store layout do not significantly affect purchasing decisions.